PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN DURIAN TARUNG - Maiza, Fitria; Rismen, Sefna; Mardiyah, Ainil (Pendidikan Matematika, 2013)
The background of this research was studentsâ comprehension of mathematical concepts which was still low at eight grades in MTsN Durian Tarung. The purpose of this research was to find out whether studentsâ comprehension of mathematical concepts by using TAI Cooperative Learning was better than a conventional learning. The research was an Experimental Research with random arrangement toward the subject of this research. The research population is all Eight Grade students. The samples were chosen randomly. The instrument used in this research is essay posttest with indicator comprehension concept. Data analysis technique used was one party t-test. Based on the result of t-test is Â  = 3,67, it means better thanÂ  Â = 1,645. In result, the hypothesis is accepted, studentsâ comprehension of mathematical concepts by using TAI Cooperative Learning was better than a conventional learning, with 95% credibility